Penerapan Pembelajaran Kooperatif Model Index Card Match untuk Meningkatkan Hasil Belajar Biologi - Asnawati, Asnawati; Rahim, Muhammad Salam (COGNITIVISM: Journal of Educational Research and Development, 2025)
This study aims to determine the improvement of biology learning outcomes in grade VIII of SMP As-Salam Ambon through the application of the Index Card Match model of cooperative learning. The type of research used is Classroom Action Research (PTK) which consists of four stages, namely action planning, action implementation, observation, and reflection with 17 subjects. The data collection technique is by conducting tests and observations. The data analysis of this study was carried out descriptively. The results of data analysis were obtained that the application of cooperative learning of the index card match model can improve the learning outcomes of students in grade VIII of SMP As-Salam Ambon on the material of the circulatory system in humans. This result is aimed at the increase in test results in cycle I, and cycle II which is carried out with the cooperative learning model of the index card match model, namely in the initial test of student learning completeness, which is 11.76%, after taking action using the cooperative learning model of the index card match, the success rate achieved by students in cycle I increased to 58.82%, then in cycle II it increased again to 100%.